Continuous ambulatory peritoneal dialysis for infantile chronic renal failure (A case report). - Pungky AK Pungky AK (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2001)
A two month old male infant with lethargy, vomiting, and loss of body weight was referred to Kobe University Hospital, Kobe, Japan. He had increased levels of BUN and serum creatinine, and severe metabolic acidosis. Ultrasonography exhibited hypoplasia kidney. Treatment with continuous ambulatory peritoneal dialysis (CAPD), recombinant human erythropoietin, and recombinant human growth hormone was started immediately on the admission day. All of his symptoms were disappeared and he grew up well. He was discharged 3 months after admission and he had been treated with the above therapy in Out Patient Clinic. CAPD on CRF patient is the most essential management. CAPD system should be introduced to save infants and children with chronic renal failure in Indonesia.Keywords : chronic renal failure - peritoneal dialysis — infant - hypoplasia kidney - recombinant growth hormone